A relação entre trabalho, cooperação e solidariedade na formação da Cooperativa Colonizadora Multiativa Fernheim Ltda no Chaco Paraguaio - Luana Jamayna Gellert; Paula Cecilia Pérez Reyes; Valmor Schiochet (Ciências Sociais Unisinos)
Work, cooperation and solidarity are values that together that enable people to earn a living as an alternative to the exacerbated competition fostered by the capitalist model. The article analyzes the case of the Fernheim Cooperative, located in the Paraguayan Chaco, which is desert-like area with a small population. This analysis demonstrates how an experiment strongly based on these three values: work, cooperation and solidarity, can last over time and change the reality of a region.